Remarks on numerical estimation of the critical impact velocity in shear - Klósak, Maciej; Łodygowski, Tomasz; Klepaczko, Janusz R. (Computer Assisted Methods in Engineering and Science, 2001)
A phenomenon called the Critical Impact Velocity (CIV), which is directly related to material behaviour under dynamic loads, is of special interest in this paper. Deformation trapping due to thermoplastic instability caused by the propagation of plastic waves is the main physical reasons for the CIV. This critical value of shear velocity should be considered as a material constant, but it is difficult to estimate due to complicated material response. Analytical approaches may only provide some preliminary estimates, because they are based on simple constitutive relations. On the other hand, experimental techniques are more reliable, but then there exist problems in specimen design. Numerical techniques such as FE method offer a possibility to treat the problem in a more general aspect. Numerical results obtained in the environment of ABAQUS code demonstrate the role to be played by computer simulations as compared to the analytical and experimental findings. The CIV in shear is studied for the case of martensitic steel VAR4340, and the FE models are based on geometry of the Modified Double Shear specimen (MDS). Thus, the principal questions are formulated as follows: to which extent the analytical approach approximate the CIV, what is the role of experimental results and what information can be obtained after numerical simulations.